A Conceptual Framework for Tax Non-Compliance Studies in a Muslim Country: A Proposed Framework for The Case Of Yemen. (Global Business Management Review (GBMR), 2022)
The problem of tax noncompliance is widely described as a serious global phenomenon, especially in developing and least developing countries. Literatures indicate a number of factors that could possibly influence tax noncompliance behaviour but there is no single theory that can explain the phenomenon of tax noncompliance behaviour. Thus, researchers suggested that theories from sociology, psychology and economy could be useful in explaining tax behaviour. Perception and attitude of taxpayers are among the factors contributing towards compliance behaviour. In this regard, empirical evidence indicates that taxpayers act according to their belief and attitudes. Nevertheless, the specific attitude/view of Muslims towards tax has not been considered. Consequently, the purpose of this paper is to discuss the theoretical link between the influence of Islamic religious perspective and tax noncompliance behaviour. Furthermore, tax service quality, public governance quality and tax system structure, which are perceived as relevant to developing and least developing countries, were taken into consideration in the proposed framework. The paper concluded by urging future researchers to consider the relevancy of the Muslim-majority community in the future tax noncompliance studies.